2017
DOI: 10.1146/annurev-physchem-040215-112634
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Bilayers: Stability and Encapsulation of Nanoparticles

Abstract: Nanoparticles are widely studied for their potential medical uses in diagnostics and therapeutics. The interface between a nanoparticle and its target has been a focus of research, both to guide the nanoparticle and to prevent it from deactivating. Given nature's frequent use of phospholipid vesicles as carriers, much attention has been paid to phospholipids as a vehicle for drug delivery. The physical chemistry of bilayer formation and nanoparticle encapsulation is complex, touching on fundamental properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 140 publications
0
39
0
Order By: Relevance
“…Third, nanoparticles can be wrapped by lipid molecules, which behave similarly to surfactants. The interactions between lipid membranes and colloidal particles depend on many factors, e.g., the surface charge of particles and liposomes, the size of the vesicles and particles, membrane composition, and surface composition of the particles [187]. Many theoretical studies described the interaction between colloidal particles and lipid membranes.…”
Section: Interactions Between Gold Nanoparticles and Lipid Bilayersmentioning
confidence: 99%
“…Third, nanoparticles can be wrapped by lipid molecules, which behave similarly to surfactants. The interactions between lipid membranes and colloidal particles depend on many factors, e.g., the surface charge of particles and liposomes, the size of the vesicles and particles, membrane composition, and surface composition of the particles [187]. Many theoretical studies described the interaction between colloidal particles and lipid membranes.…”
Section: Interactions Between Gold Nanoparticles and Lipid Bilayersmentioning
confidence: 99%
“…Third, liposomal preparations prepared by sonication or membrane extrusion are heterogeneous in size, ranging from 300 nm to 20 microns [22], and production of homogeneously sized liposomes requires some form of post-formation processing [23]. Finally, unless further modified, liposomal formulations are unstable in biological media due to pH and ionic strength issues and are thermodynamically unstable with regard to morphology, precluding long-term storage of liposome suspensions [24]. Accordingly, most liposomal preparations require either reconstitution immediately prior to use or addition of additional components to the formulation mixture to stabilize the liposome in the vesicle morphology.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have proved that nanoparticles stability not only depends on the repulsive electrostatic double layer (zeta potential value) but also is closely related to the van der Waals and structural forces (surface functionalization) [40][41][42]. Surface functionalization can reduce the probability of nanostructure aggrega-tion, prevent the nonspecific adsorption, and increase the steric stability of liposomes [42][43][44]. For instance, Smith et al found that PEG modification greatly improved the stability of DOTAP liposomes and DOP liposomes [45].…”
Section: Resultsmentioning
confidence: 99%